Arsenic Accumulation and Speciation in Transplanted Autumn Rice as Influenced by Source of Irrigation and Organic Manures - Sinha, B.; Bhattacharyya, K. (International Journal of Bio-resource and Stress Management, 2023)
An effort has been made, through the present study, to take an account of arsenic (As) speciation in rice in the arsenic affected villages of Chakdaha block, Nadia district, West Bengal, India having an arsenic concentration of irrigation water drifted from the shallow tube wells 0.32 mg L-1. It appeared very clear from the present study that inorganic arsenic shared maximum arsenic load in rice straw while in grains it is considerably low. As species recovered from rice straw and grain are principally As-V and As-III and. Rice grain As has been found to be principally As-III while in straw As-V predominated over As-III. The results also shows that arsenic accumulation in different parts of rice remained in an order of root>leaf>shoot>grain. It was observed that incorporation of organic manures significantly reduced the arsenic uptake by different plant parts of rice is more pronounced and consistent with FYM and Vermicompost. Discussion of the health risk of As in rice has largely been based on its inorganic arsenic content because these species have generally been considered to be more toxic than MMA and DMA and can be directly compared to As in drinking water, assuming equal bioavailability of inorganic As in the rice matrix and in water. The maximum dietary risk of exposure to inorganic arsenic through transplanted autumn rice in the present experiment was calculated to be almost 700 % of PTWI (Provisional Tolerable Weekly Intake) for an adult of 60 kg body weight.